Sustainable production of highly conductive multilayer graphene ink for wireless connectivity and IoT applications. Issue 1 (December 2018) - Pan, Kewen; Fan, Yangyang; Leng, Ting; Li, Jiashen; Xin, Zhiying; Zhang, Jiawei; Hao, Ling; Gallop, John; Novoselov, Kostya; Hu, Zhirun
Abstract Printed electronics offer a breakthrough in the penetration of information technology into everyday life. The possibility of printing electronic circuits will further promote the spread of the Internet of Things applications. Inks based on graphene have a chance to dominate this technology, as they potentially can be low cost and applied directly on materials like textile and paper. Here we report the environmentally sustainable route of production of graphene ink suitable for screen-printing technology. The use of non-toxic solvent Dihydrolevoglucosenone (Cyrene) significantly speeds up and reduces the cost of the liquid phase exfoliation of graphite. Printing with our ink results in very high conductivity (7.13 × 104 S m−1 ) devices, which allows us to produce wireless connectivity antenna operational from MHz to tens of GHz, which can be used for wireless data communication and energy harvesting, which brings us very close to the ubiquitous use of printed graphene technology for such applications. Printed conductive inks show promise for future electronic device applications. Here, the authors report synthesis of graphene inks with conductivity of 7.13 × 10^4 S/m by Cyrene assisted liquid phase exfoliation, and their applications in data communication and RF energy harvesting.